Meningkatkan Komunikasi Matematis yang Efektif: Pengaruh Penerapan Model Role-Playing Berbantu GeoGebra dalam Menyelesaikan Soal Setara PISA - Siti Fitri Diaroh; Hamidah Suryani Lukman; Nur Agustiani (LPPM Universitas Advent Indonesia, 2023)
The mathematical communication abilities of students play a significant role in understanding and conveying mathematical concepts. This study aims to compare the implementation of three instructional models, namely the Role-Playing Model with GeoGebra assistance, the Role-Playing Model, and the Direct Instruction Model, on students' mathematical communication abilities in solving PISA-equivalent problems. The research method employed is quantitative with a Quasi-Experimental design using the Nonequivalent Control Group Design. The population of this study consists of eighth-grade students at MTs Nurul Huda. Sample selection was conducted using purposive sampling. The sample consists of three classes: VIII B (experimental class 1) with 24 students, VIII C (experimental class 2) with 23 students, and VIII A (control class) with 20 students. The research instruments comprise pretest and posttest tests to measure students' mathematical communication abilities in solving PISA-equivalent problems. Additionally, observation sheets for teachers and students were used as non-test instruments. Quantitative data analysis was performed using parametric statistics for the balance test, namely a one-way ANOVA with the prerequisite of normality and homogeneity tests. The results of the analysis indicate that the Role-Playing Model with GeoGebra assistance is superior in improving students' mathematical communication abilities in solving PISA-equivalent problems compared to the other two instructional models.